Asthma management: A new phenotype-based approach using presence of eosinophilia and allergy - Terl, M; Sedlák, V; Cap, P; Dvořáková, R; Kašák, V; Kočí, T; Novotna, B; Seberova, E; Panzner, P; Zindr, V (Allergy, 2017)
Asthma is a heterogeneous disease. The Czech Pneumology and Allergology Societies commissioned 10 experts to review the literature and create joint national guidelines for managing asthma, reflecting this heterogeneity. The aim was to develop an easy-to-use diagnostic strategy as a rational approach to the widening opportunities for the use of phenotype-targeted therapy. The guidelines were presented on websites for public comments by members of both the societies. The reviewers' comments contributed to creating the final version of the guidelines. The key hallmark of the diagnostic approach is the pragmatic concept, which assesses the presence of allergy and eosinophilia in each asthmatic patient. The guidelines define three clinically relevant asthma phenotypes: eosinophilic allergic asthma, eosinophilic nonallergic asthma and noneosinophilic nonallergic asthma. The resulting multifunctional classification describing the severity, level of control and phenotype is the starting point for a comprehensive treatment strategy. The level of control is constantly confronted with the intensity of the common stepwise pharmacotherapy, and the concurrently included phenotyping is essential for phenotype-specific therapy. The concept of the asthma approach with assessing the presence of eosinophilia and allergy provides a way for more precise diagnosis, which is a prerequisite for using widening options of personalized therapy.
Keywords: phenotype-specific therapy; eozinofilie; Severity of Illness Index; eosinophilia; Eosinophilia; Asthma; bronchiální astma; Humans; Hypersensitivity; Phenotype; allergy; stupeň závažnosti nemoci; lidé; individualizovaná medicína; asthma heterogeneity; fenotyp; Precision Medicine; alergie